Resolution of racemic Vigabatrin using tartaric acid. Issue 17 (2nd September 2018) - Karumanchi, Kishore; Kumar Natarajan, Senthil; Moturu, Krishna Murthy V. R.; Chavakula, Ramadas; Korupolu, Raghu Babu; Bonige, Kishore Babu
Abstract: An efficient and simple resolution methodology for the preparation of ( S )- and ( R )-Vigabatrin has been developed. In addition, a method of preparation for the novel compounds Vigabatrin-l -tartarate and Vigabatrin-d -tartarate is also described. The title compounds have been synthesized via resolution of Vigabatrin using commercially availablel -(+)- andd -(−)-tartaric acids respectively. Graphical Abstract: